Endocrine response to lactate infusion during pentobarbitone anaesthesia - Luna, S. P.L. [UNESP]; Taylor, P. M. (Elsevier, 1996)
Lactic acid was infused iv in 6 Welsh ponies during pentobarbitone anaesthesia to investigate whether lactate triggers the pituitary-adrenal response to anaesthesia. Ponies were premedicated with acepromazine and anaesthesia was induced with pentobarbitone iv and maintained with pentobarbitone/oxygen for 2 h. Immediately after induction, 3% L(+) lactic acid infusion was started and adjusted to maintain plasma lactate concentration between 2 and 2.5 mmol/l. Cardiorespiratory function, temperature. PCV, plasma glucose, lactate, βendorphin, ACTH, cortisol and catecholamine concentrations were measured before, during and after anaesthesia. Hypothermia, reduced PCV, slight hypotension (minimum value 84 ± 6 mmHg 20 min after induction of anaesthesia), hyperoxia and marked bradypnoea developed during anaesthesia. No acidaemia occurred. Plasma glucose concentration increased at the end of anaesthesia. There were no changes in plasma ACTH, cortisol and catecholamine concentrations, but plasma & endorphin increased after induction until the end of anaesthesia. There was a correlation between plasma lactate and β-endorphin concentrations (P<0.001, r=0.63), which may suggest that lactate stimulates βendorphin release. Beta-endorphin was apparently secreted independently from ACTH and appears to be a sensitive marker of a stress response. © 1996 Wiley. All rights reserved.